Consumer purchase intention on life insurance among Cambodians - Lenghouy Heng; Soun Hong (Southeast Asian Journal of Service Management, 2026)
This study investigates factors influencing life insurance purchase intention among residents of Phnom Penh, Cambodia, amid a growing yet underdeveloped insurance industry with low penetration. Guided by two research questions—what factors influence purchase intention and what challenges consumers face—the study aims to examine these drivers and identify key barriers to adoption. A quantitative approach was used, collecting data from 386 respondents through structured questionnaires. Results showed that all four examined variables significantly influence purchase intention, with trust in insurance providers being the most influential, highlighting the importance of credibility and transparency. Consumer knowledge and social influence also showed strong positive effects, while perceived risk positively influenced intention, suggesting that risk awareness motivates protective purchasing behavior. The study also identified key barriers to adoption, including distrust in providers fulfilling promises, pricing concerns, limited awareness, complicated claims processes, financial constraints, poor service experience, and dissatisfaction with insurance packaging. These findings highlight the need for reforms in communication, transparency, and service delivery. The study offers practical implications for insurers, policymakers, and marketers, suggesting that enhancing consumer education, building trust, addressing perceived risks, and leveraging social influence can improve life insurance adoption in Cambodia.